Analisis Sistem Upah Di Toko Bintang Variasi Menurut Perspektif Ekonomi Islam - Anggita Aprila Nanda; Deni Panca Ramadan; Helga Fadhillah Rohman; Carmidah Carmidah (Pusat Riset dan Inovasi Nasional, 2023)
The owner of the company must be able to act fairly towards the employees who are owned by the company, because every employee has the right to get appreciation, performance appreciation, and get fair treatment from the owner of the company as a return for his services and dedication to the company. If viewed from the perspective of Islamic Economics, good ethics and those recommended by the Islamic religion in business must be free from elements of usury, cheating, uncertainty, fraud or manipulation, and acts of injustice. This study uses a descriptive approach, in which the researcher describes systematically and facts about the wage system applied to Bintang Variations Store. in data sources in this study are divided into two types, namely primary data and secondary data. From the salary system implemented by Bintang Variations Store, it is a wage system using the Fiqh Muamalah Science approach, namely Ijarah because it relates to salaries and human labor. In conclusion, the wage system implemented at the Bintang Variation Store in providing salaries to its employees is in accordance with Islamic Shariat.